Analysis of Implementation and Result of Analytical Chemistry Instrument Labwork - Haryani, Sri; Dewi, Siti Herlina; Wardani, Sri; Prasetya , Agung Tri (KnE Social Sciences, 2019)
The purpose of this research was to obtain an overview about the implementation of analytical chemistry instrument practicum and its learning outcome. The subject of this research was the students of chemistry education program of FMIPA UNNES who took Analytical Chemistry Instrument Practice course. Observations, interviews and ﬁeld noteswerecarriedoutonpracticumrelatedtothemethodofassessment,theactivities of lecturer and students during class, as well as the practical manual. Meanwhile, the instruments that used for learning outcome were verbal pretest, an observation sheet to assess the practicum result, verbal questions when students reported observational data, and assessment sheet of practicum report and its rubric. The assessment was carried out in writing containing the mastery of the concept and knowledge of the procedure, the results of practicum observation data, and the practicum report. The practicum report was assessed without using criteria that are known to students, so that it lacks continuous feedback. In general, students do not understand the basic concepts related to practicum, were less able to explain what was done and were less able to explain the observed tendency, and even did not realize that the measurement results were far from expectation. In the case of writing report, there was a weakness in correlating the data of observations, discussions, and conclusions. It was necessary to pursue a practicum activity that in addition to developing basic skills in conducting experimentsandimprovingunderstandingofconcepts,alsodevelopsproblem-solving skill, and the formation of scientiﬁc attitudes, all of which are netted in well-prepared assessments. Keywords: Practicum, analytical chemistry instrument, result of practicum learning, practicum assessment.